Wiraga Wirama Wirasa Dalam Tari Tradisi Gaya Surakarta - Dwi Maryani (Gelar : Jurnal Seni Budaya, 2007)
Javanese traditional dances of Surakarta style are one of the ancestor’s  heritage owned by the king so that abdi dalem (the royal servants), especialy abdi  dalem taya in the court of Surakarta remain obeying the king’s order. In other  words, traditional art of Surakarta existing in the court of Surakarta still go on  according to the handbook or guidelines applicable at that time. To be a good Javanese  dancer, someone has to have a good knowledge of three basic concepts, namely, wiraga,  wirama, and wirasa. A Javanese dancer, especially that of  surakarta style, should  pay attention to the series and forms of movements, and dance structure and call  adjust the kind and character of the dance to the rhythm of gending (melody). A  dance who has acquired skills in wiraga, wirama, and wirasa will dance gracefully,  not stiffly. He will not make forced movements; everything looks smooth and flows in  enjoyable rhythm. He moves seriously but does not look strained.Keywords: Wiraga Wirama Wirasa, Traditional Dance.